Liabilities of directors under Malaysian insolvency laws and recovery of assets during corporate insolvency - Aishah Bidin (Fakulti Undang - Undang, 2004)

(untitled)
Under the legal regime governing Malaysian companies, insolvency is defined as a state of affairs where the company is unable to meet its financial obligation namely to pay its debt. A bound of director is usually entrusted with the responsibilities. Liabilities can in certain circumstances be attached to the directors when the company goes into liquidation. In such situation, the rights of creditors emerge which gave rise to legal issues in relation to duties of directors to creditors. These liabilities can take in the form of personal can also be held criminally liable for any failure to observe statutory requirements or for dishonesty and fraudulent conduct with respect to the company. This paper will evaluate the extent of the directors’ duties and liabilities during insolvency and issues on recovery of assets and claims by creditors during insolvency